(untitled) (Estudios de Historia de España, 2021)
The approach to Spanish esotericism in the early-modern period continues to be notably marginal among specialists. At the crossroads of cultural history and political history, we investigate both the characteristics of esoteric practices and representations in 16th century Spain and the representational struggles between the hostile discourses of Christian orthodoxy and the apologetics of esotericists. We approach the “Silva de varia lección” (1540) by Pedro Mexía (who was to be appointed in 1548 Imperial Chronicler of Carlos V) to focus both on the peculiarities of his specific representation of magic-astrological rings and on the characteristics of his apologetic speech regarding the criticism of Christian orthodoxy.